Scientific reasoning and views on the nature of scientific inquiry: testing a new framework to understand and model epistemic cognition in science. Issue 16 (1st November 2020) - Reith, Marco; Nehring, Andreas
ABSTRACT: Against the background of many studies focusing either on scientific reasoning or views on the nature of scientific inquiry (NOSI), the aim of this article is to present and empirically analyse a framework that associates these central science education constructs. Based on the idea of inquiry methods, the ScieNo- framework includes three scientific reasoning competencies (' Scie ') and ten naïve and informed NOSI views (' No ') that can be aligned on a theoretical level. We test this alignment using data from a quantitative cross-sectional study. In this study, internationally published instruments on scientific reasoning and NOSI views were administered in a sample of 802 students. We estimate structural equation models (SEM) that encompass correlations between scientific reasoning competencies and NOSI views. In order to control for effects of schooling in a second step, we included the grade level as a predictor into these models and checked whether the correlations were stable. The results confirm small to high positive and negative correlations between informed and naïve NOSI views and the scientific reasoning competencies that match the theory-based assumption. We interpret these as a first quantitative confirmation of the ScieNo -framework and open up further perspectives on usage of the framework for science education purposes and for future science education research.